1994
DOI: 10.1111/j.1399-302x.1994.tb00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal action of tachyplesin I against oral streptococci

Abstract: Tachyplesin I, a polycationic antimicrobial peptide isolated from hemocytes of horseshoe crabs, kills bacteria by disrupting the membrane potential of the cytoplasmic membrane. The present study shows that, among 36 oral streptococcal strains, 12 of 21 Streptococcus sanguis, 3 Streptococcus mutans, 9 Streptococcus salivarius and 3 Streptococcus milleri strains were susceptible to tachyplesin I, whereas 9 S. sanguis strains were resistant. Interestingly, these resistant strains include the clinical isolates fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Further exploration of these compounds may lead to the development of valuable medicines for treating, among others, erectogenic conditions [76][77][78], botulism [97,98], malignant neoplasms [114,116,222,223], autoimmune disorders [133], microbial [161,165,210,215,245] and parasitic infections [147], and chronic pain [207], as well as improved bacterial endotoxin detection [159] and innovative sunscreens [178]. These advances are much needed when considering the high global incidence of erectogenic conditions [250], autoimmune disorders [251], and cancer [252], the worldwide threat of bioterrorism [99], and the increasing resistance of microbial [253] and parasitic infections [254] to exisiting medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further exploration of these compounds may lead to the development of valuable medicines for treating, among others, erectogenic conditions [76][77][78], botulism [97,98], malignant neoplasms [114,116,222,223], autoimmune disorders [133], microbial [161,165,210,215,245] and parasitic infections [147], and chronic pain [207], as well as improved bacterial endotoxin detection [159] and innovative sunscreens [178]. These advances are much needed when considering the high global incidence of erectogenic conditions [250], autoimmune disorders [251], and cancer [252], the worldwide threat of bioterrorism [99], and the increasing resistance of microbial [253] and parasitic infections [254] to exisiting medications.…”
Section: Discussionmentioning
confidence: 99%
“…They presumably play a role in the protection of horseshoe crabs from invading microorganisms. Indeed, these compounds were found to inhibit the growth of both Gram-negative and -positive bacteria at low concentrations [161,164,165]. Due to their small size, positive net charge, and amphiphatic character, they are able to insert into bacterial membranes and to interact with the negatively charged lipopolysaccharides in bacterial membranes [160][161][162]164] such as lipopolysaccharides [166].…”
Section: Horseshoe Crab-derived Antibioticsmentioning
confidence: 99%
“…Among these 17 alpha amino acid residues, 4 cysteine residues constitute two disulfide bonds that contribute to the hemolytic ability of TP I in blood cells [2]. Furthermore, research has shown that TP I is active against both Gram-positive and Gram-negative bacteria [3], fungi [4], viruses [5], and cancer cells [6]. The peptide also interacts with DNA and inhibits the synthesis of macromolecules.…”
Section: Introductionmentioning
confidence: 99%
“…Tachyplesin I exerts variable bactericidal activities against oral Gram-positive streptococciwhich are potential dental and mucosal pathogensin aerobic broth culture (13). Protegrin isoforms, including PG-1, D-PG-1, PG-2, PG-3 and PG-5, were highly microbicidal against A. actinomycetemcomitans and the Capnocytophaga spp.…”
mentioning
confidence: 99%